Evaluation of properties and aging resistance of epoxy asphalt composite modified by ultraviolet absorber - Wang, Qichang (2023)
This research investigated the effect of ultraviolet absorber (UV-531) on the properties of epoxy asphalt (EA) binders. EA binders were modified by adding UV-531 absorber at contents of 0, 0.3, 0.6, 0.9, and 1.2 wt%, and composites were then subjected to ultraviolet (UV)-based aging, including UV, oxygen, and heat treatment. Laboratory tests were conducted to assess UV absorption, viscosity, mechanical parameters, contact angle, microstructure, and chemical functional groups of absorber-modified EA composites before and after aging. The results showed that the addition of UV-531 resulted in enhanced UV absorption capacity, lower initial viscosity, and longer allowable application time for EA composites. The UV-531 absorber has good compatibility with EA binders and does not weaken the performance of EA binders. From anti-aging perspective, UV-531 absorber effectively delayed the degradation of the physical, mechanical, and chemical structures of EA composites. The breakage of alkyl and ester groups of EA composites containing absorber was significantly reduced under aging conditions. Overall, the presence of UV-531 retarded severe performance deterioration in EA composite. Considering aging improvement and economic cost, it is recommended to use a content of 0.9 wt% UV-531 absorber as an anti-aging agent for EA composites.